(untitled) (Innovaciones Educativas, 2019)
This article summarizes the process carried out to promote communicative competence in speaking skills; it was developed through the implementation of teaching strategies based on the learning styles proposed by Kolb in his model of the Experiential Learning Theory of 1984. This case study was carried out during the last semester (July to December), in 2014; in fact, four beginner EFL students were the research participants. To collect data, three instruments were administered: a checklist, a scoring sheet and a questionnaire. The data gathered was analyzed and triangulated through three pre-established categories of analysis: participants’ learning styles, learners’ oral performance before conducting the research, and students’ communicative competence in speaking skills after the implementation of teaching strategies specifically based on the identified learning styles from Kolb’s model of the Experiential Learning Theory of 1984. Generally, the findings obtained show the effectiveness of the teaching strategies implemented in regards to the identified learning types; these strategies aimed to help students improve their communicative competence in speaking skills.